CAPACITY DEVELOPMENT OF STATE APPARATUS IN EFFECTIVE AND EFFICIENT STATE ADMINISTRATION - Utami, Cahyaning Bhakti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze strategies for developing the capacity of state officials in effective and efficient state administration. Along with the dynamics of globalization and digitalization, state officials are required to increase their competence and professionalism to face the challenges of modern bureaucracy. This study uses the method Systematic Literature Review (SLR) to review various previous research that is relevant to developing the capacity of state apparatus, the effectiveness of public administration, and innovation in government governance. The research results show that developing the capacity of state apparatus requires a comprehensive approach, including increasing technical competence, strengthening bureaucratic ethical values, and utilizing information technology in public administration. Apart from that, bureaucratic reform that is oriented towards public services is a key factor in creating a state administration system that is responsive, transparent and accountable.The discussion in this study highlights the importance of synergy between regulations, education and training, as well as data-based policy implementation in increasing the effectiveness of state administration. In conclusion, capacity development of state apparatus must be carried out in a sustainable manner with the support of policies that are adaptive to changing times. Recommendations from this study include improving technology-based training programs, reforming the performance evaluation system, and improving a work culture oriented towards community service.